Spiritual Strengthening Model for Street Children Education Between the Hope and Challenges of ASEAN Economic Community (MEA) - Yapandi Yapandi (Universitas Tanjungpura, 2018)
This paper argues that building a community of street children through a spiritual model can be developed in West Kalimantan to strengthen the values of monotheism. By exposing and simultaneously evaluating the current model of street child development through Talcott Parsons functionalism to see how individuals and communities integrate into a social system, and the concept of spiritual model (and spiritual intelligence) a la Danah Zohar as a form of tauhidullah values development and higher goals in street children life, the model of empowerment through the development of spiritual models needs to be placed in a sociological, social and pedagogical setting for access to educational resources and political systems. The issues and problems of street children are never separated from local identity (identity politics), and individual and group characters. Voluntaristically accepting social norms and values as such, humans are actively involved in social exchanges. Likewise, instead of one-dimensional, the individual's identity is liquid and multidimensional.